Village politics can be murder - Dams, Jeanne M. (Dams, Jeanne M. Dorothy Martin mysteries., 2024)
A trip to the Lake District proves to be anything but idyllic when Dorothy and Alan investigate a mysterious death. Dorothy Martin and her husband, retired chief constable Alan Nesbitt, jump at the chance to holiday in the beautiful Lake District when Alan's old friend, Christopher Prideaux, invites them to visit him in Grasmere. A party at Christopher's cottage is the perfect way to meet the locals, but one stands out - accountant Donald Atkinson, an egoist hoping to become a politician, clearly isn't popular among his fellow villagers. When he's found mysteriously dead during the Fell Race, could his demise be due to a sudden, fatal medical emergency, or was it murder? Dorothy and Alan find themselves catapulted into a disturbing case that will lead them back in time, and to a terrible, scandalous secret that someone is determined to keep hidden.